Is Your Retailer a Friend or Foe: When Should the Manufacturer Allow Its Retailer to Refurbish?. Issue 9 (2nd September 2021) - Timoumi, Ahmed; Singh, Narendra; Kumar, Subodha
Abstract : Refurbishing of used products is increasingly being recognized as a value recovery strategy in sustainable operations. Hence, manufacturers, retailers, as well as third‐party firms, engage in refurbishing. Manufacturers, to some extent, can deter other players from refurbishing through various means such as product design, intellectual property, and restricting access to spare parts and diagnostic tools. While previous research has extensively examined the question of whether a manufacturer should allow an independent third‐party player to refurbish used products, the question of whether a manufacturer should allow his retailer to refurbish them, to our knowledge, remains unanswered. In this study, we examine whether a manufacturer should refurbish used products himself or allow his retailer to refurbish them. We compare two closed‐loop supply chain structures: Model‐M, where the manufacturer refurbishes used products; and Model‐R, where the retailer refurbishes. In a two‐period setting, new products are sold in both periods and some of the first‐period products are refurbishable in the second period. We show that when either (i) the refurbishability of used products is low and the attractiveness of refurbishing (value of the refurbished product as compared to the refurbishing cost) is either moderate or sufficiently high, or (ii) the refurbishability is high and the attractiveness of refurbishing is moderate, the manufacturer, despite forgoing profits and facing competition from refurbished products, is better off with letting the retailer refurbish used products (Model‐R) than with refurbishing them himself (Model‐M). Identifying a novel mechanism through which the manufacturer benefits in Model‐R is our key theoretical contribution to the closed‐loop supply chain literature. Moreover, we provide some useful and interesting insights to policymakers related to customer welfare and the environment. We also analyze the performances of these models (Model‐M and Model‐R) in terms of supply chain efficiency. In addition, we discuss how some of our key results change if a third‐party refurbisher coexists with the manufacturer and the retailer. Our results not only support some of the current policies and practices but also shed some light on their limitations and suggest some avenues for improvement.